Factors Associated With Zika Virus Information on County Health Department Websites in the State of Texas [11M]. (May 2017) - Cuvillier, James; Page-Ramsey, Sarah M.; Rodriguez, Emma; Ireland, Kayla; Adesomo, Adebayo; Ramsey, Patrick S.
Abstract : INTRODUCTION: In the United States, Texas has the third highest reported Zika case incidence (218 cases, October 2016), including 13 pregnant women. Thus, prevention is a critical public health concern. Our objective was to evaluate factors associated with availability of Zika virus information on Texas county health department websites. METHODS: We reviewed Texas county health department websites for any Zika virus information, using internal searches for "Zika" when necessary. Factors potentially associated with availability of information on the county website (birth rates, "metropolitan" designation, reported Zika cases, and designation as a county bordering Mexico) were compared between groups using a Fisher's exact test and Student t-test where appropriate. RESULTS: Of 254 counties, 35 (13.8%) reported information about Zika virus on their county health websites. Mean birth rates in counties with information about Zika were higher than counties without Zika information (14.4/1000 vs 12.5/1000, p < 0.0001). These counties were also more likely to be "metropolitan" designation (77.1% vs 25.1%, p < 0.0001) and have Zika cases (45.7% vs 1.8%, p < 0.0001). Mexican border designation was not associated with increased likelihood of publishing Zika information (2.9% vs 6.4%, p=0.70). CONCLUSION: Very few Texas county health department websites contain any information about the Zika virus. Counties with higher birth rates, "metropolitan" designation, and Zika cases are more likely to have Zika information available. Disseminating county-specific resources and instruction on Zika surveillance, prevention, and monitoring of pregnancy and infant outcomes will be vital in preparing for potential future outbreaks or viral entry to local mosquito populations.